MODELING HIGHER EDUCATION ATTRACTIVENESS TO STAND GLOBAL ENVIRONMENT - Leonel Cezar Rodrigues (Universidade Federal de Santa Catarina, 2016)
Inabilities to deal with the changing environment may lead Higher Education Institutions (HEI) to loose institution al attractiveness. Digital transformation requires global insertion as essential feature to institutional attractiveness. Processes for international education seem to lack the links between real environmental trends and the internal capabilities to global education. HEI managers may approach endeavors to internationalize education combining ambidextrous strategy supported by consolidated resilience capabilities. The latest ones refer to building internal value attributes to increase institutional attractiv eness assuring solid standing in the global environment. In this article, a theoretical essay, we approach the problem of creating resilience as a way of backing up ambidexterity to generate institutional attractiveness. The set of value attributes, on the other hand, may originate strategic routes to strengthen internal competences and to make the institution more attractive, as a dynamic capability.